Chromosomal abnormalities in spontan eous abortions - Mora Alferez, A. Pamela (2016)
Introduction: 15 to 20% of clinical pregnancies end in spontaneous abortion and 25% of women will have an abortion during her life. Over 50% of cases of spontaneous abortions carry one or more chromosomal abnormalities. Objectives: To determine the frequency of chromosomal abnormalities in spontaneous abortions and its relationship with maternal age and other parameters like gestational age. Design: Transversal, descriptive study on secondary database. Setting: Cytogenetic Laboratory of the Instituto de Medicina Genética. Material: Samples of spontaneous abortions. Methods: Database analysis of 2319 samples of spontaneous abortions received between January 1996 and December 2013. Main outcome measures: Frequency of chromosomal abnormalities. Results: Of the 2 319 samples analyzed 1 595 showed abnormal karyotype (68.8%). Of all the numerical abnormalities (1 395/1 595) described, 83.2% consisted in aneuploidy and 16.8% polyploidy. Mosaicisms were present in 5.5% (87/1 595) and structural anomalies in 3.5% (56/1 595). Dependence was found between maternal age and trisomies (X2 p<0.05). Conclusions: 68.8% of abortions showed a chromosomal alteration; the aneuploidies were the most common numerical abnormalities with predominance of trisomies (58.4%) which were associated with increased maternal age.